Rethinking food crisis responses: MENA launch of the CGIAR Initiative on Fragility, Conflict, and Migration - CGIAR Initiative on Fragility, Conflict, and Migration (CGIAR, 2023)
In 2022, the world faced multiple crises. Disruptions to food systems continued due to the protracted pandemic, natural disasters, civil unrest, political instability, and the impacts of climate change. The situation was exacerbated by the war in Ukraine, which created a global food and fertilizer crisis. The Middle East and North Africa (MENA) region, which is among the most vulnerable to climate change and water scarcity, was heavily affected.